Co-teaching praxis as an interdisciplinary experience in Natural Sciences teaching - Dalana Campos Muscardi; Vivian Estevam Cornélio (Universidade Federal do Norte do Tocantins, 2020)
Although education in rural areas is already robust, especially in relation to basic education, the graduation courses regarding to teacher formation to this specific area are still young in the brazilian educational scenario. This aspect is being the scene of epistemological, didactic and many other discussions that imply the teaching action. We teach natural sciences in a degree course in education in rural areas in the Northern University Center of Espírito Santo, Federal University of Espírito Santo and we discuss these and other issues, such as the teaching training by knowledge area, overlapping and incorporating the debates in our teaching practice. Therefore, we present in this article our co-teaching experience and we discuss its challenges and overcoming during teaching a discipline composed by contents of biology and chemistry. The discipline, called "Introduction to cell biology and life chemistry" was created by two teachers and had 60 hours of theory, taught during one semester. The discipline and its evaluation activities were elaborated to integrate biology and chemistry contents, to turn interdisciplinarity as possible to realize. We report here the whole process of co-teaching, which began with the collaborative conception and creation of the discipline, moving forward to its execution, the elaboration of evaluative activities and finalizing with the reflection and the writing of this paper. Our experience revels the importance of interdisciplinarity and co-teaching as a possibility of breaking the fragmented formation in higher education.